Pengembangan Media Pembelajaran Berbantuan Note Taking untuk Meningkatkan Keterampilan dalam Menulis Cerpen pada Siswa Kelas XI SMK Musda Perbaungan - Parwati, Juliya; Rita, Rita; Safina, Nila (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aimed to enhance short story writing skills among class XI students at SMK Musda Perbaungan. The population comprised 481 students, with a sample size of 32 students from class XI TKJ 1. Data collection involved observation, interviews, and questionnaires. Research followed the Borg and Gall's 10-stage research and development (R&D) model. Results indicated that note-taking assisted learning media could improve short story writing skills. Material experts rated the media as "Decent" (84% for expert 1, 78% for expert 2), while media experts rated it as "Very Decent" (91% for expert 1, 90% for expert 2). A field test with 32 students showed the effectiveness of learning media, particularly Google Keep, with an "Effective" rating of 80.09% for short story writing evaluation. This underscores the potential of note-taking assisted learning media in enhancing writing skills, suggesting its viability as an effective tool in classroom instruction for narrative composition.